PERBEDAAN PENERAPAN STANDAR ISLAMIC STOCK SCREENING DAN SOCIAL ENVIRONMENT INDEX TERHADAP KINERJA PORTOFOLIO SAHAM BEI - Balgis, Putri Dona; Fitrijanti, Tettet; Sukmadilaga, Citra (APSSAI, 2021)
This research examined differences of portfolio performance before adding indicator of social environment index from five standards (ISSI, FTSE, MSCI, DJIM and S&P) and differences of portfolio performance before and after adding indicator of social environment index.The result concludes portfolio performance using the Sharpe measure significantly different, while Treynor and Jensen Alpha did not show a significant difference of performance, there is also no significant difference of portfolio performance (Sharpe, Treynor and Jensen Alpha) before and after adding indicator social environment index. It shows that addition of indicator social environment index is not affected portfolio performance.